The Mars as the Parent Body of CI Carbonaceous Chondrites Hypothesis Re-Examined in the Light of New Data (Global Journal of Science Frontier Research, 2023)
It had been proposed that the parent body for the CI carbonaceous was the planet Mars. New data strongly supports this hypothesis. The recovery of CI-like material from the asteroid Ryugu, which orbits near Mars has confirmed the importance of CI material as a source of water for the terrestrial planets. The oxygen isotope makeup of the CI is now seen to overlap the distribution of data from the aqueously altered portions of recognized MMs (Mars Meteorites). The CI consist of completely aqueous altered ferro-magnesian silicates, carbonates and sulfates. The physical conditions that produced these materials match conditions on Early Mars, as inferred from portions of recognized ancient Mars meteorites ALH84001 and NWA 7533. Noble and Nitrogen gas isotopes match early Mars atmosphere, especially in N, Kr, Xe, and Ar isotopes with a Mars early atmosphere being composed of Chondritic Xe and Kr. The CI, despite early aqueous alteration, appear to have been, like Chassigny, preserved in a hot dry environment and have preserved entrapped Early Mars atmosphere. The CI can thus be considered to be aqueously altered remnants of a late accretion veneer that largely experienced no melt processing. Portions of this lithology have been thermally altered and formed the CY group. This Mars -CI hypothesis can be tested by chronologies of thermal alteration of the CYs. The CI are rich in organic matter, indicating that Early Mars was warm, wet, and rich in the chemical precursors of life and therefore emulated conditions that fostered life on Early Earth.